Reflections on the Teaching of Computational Methods - Li, Aijuan (IJRDO -JOURNAL OF MATHEMATICS, 2021)
Computational Methods is a basic course for science and engineering students.Combined with the usual teaching work, this paper propose two aspects: the change of teaching design and the close combination with practical problems.Two aspects should be paid attention to in the teaching process.